La fotografía como recurso para la construcción de la identidad femenina a través de las redes sociales. - Manzano Zabala, Paola Vanessa (2025)
This research aims to explore how photography can be a resource for strengthening and discovering female identity among a group of university women studying Graphic Design at the Universidad Nacional de Chimborazo, using Instagram as a platform for expression. There is a need to strengthen the self-esteem and body image of young women, as well as to discover and express identity through photography. The methodology used is descriptive, as it allowed for interaction with the women, gathering relevant information for the creation and planning of photographic content. Instruments such as surveys, interviews, photographic sheets, content analysis, and psychological support were used for its development. It is important to understand how the participants' growth has evolved throughout the project, both emotionally and physically. As a result, between 3 and 10 photographic sessions were carried out, depending on various factors such as time, personality, mental health, and identity. Each participant freely chose how to represent herself through Instagram, selecting the photographs and descriptions that best suited her.